Quality improvement project to improve cardiovascular risk screening in patients with rheumatoid arthritis - Mireille Edens; Monique Hoekstra; Harriet de Vries; Clarinda van den Bosch-Schreuder (BMJ Open Quality)
Significance and background Rheumatoid arthritis (RA) is a chronic inflammatory joint disease that is associated with an increased cardiovascular (CV) risk.Additional CV risk screening is advised in several national and international guidelines, but is performed inadequately. The CV risk screening in the Netherlands is performed by the general practitioner (GP).Purpose The aim of our project was to increase the CV risk screening of patients with RA, performed by the GP, from 46% to 65% of the selected patients of 40 years and older, within the time frame of our project (18 months).Context The project was carried out at the outpatient rheumatology clinic at Isala Zwolle, a large teaching hospital, in an area with 106 GP practices. Patients with RA, aged 40 years and older, who did not already participate in a cardiovascular risk management (CVRM) programme in general practice were included.Intervention A multicomponent improvement strategy was developed and implemented. A prospective cohort follow-up study was performed, with measurements at T=0, 6, 12, 14, 16 and 18 months. The multicomponent strategy included patient education, a standard CVRM text in the electronic patient record (EPR) as a reminder, an educational meeting about CVRM in general practice for the rheumatologists and nurses, as well as feedback sessions with the rheumatologists, showing current data.Results In our project, 784 RA patients were included. At time T=0, a CV risk analysis had been performed in the past 5 years in 46.4% of the patients with RA, who were not already participating in a CVRM protocol.This was significantly increased to 55.4% at 18 months in a prospective observational follow-up study. The primary goal, however, was not reached within the time frame of our project.Discussion The availability of patient education cards and the feedback sessions with rheumatologists significantly contributed to the improvement. The implementation of an automatic standard text in the EPR, serving as an electronic reminder, did not perform as well as was anticipated.